2015
DOI: 10.1515/bmc-2014-0041
|View full text |Cite
|
Sign up to set email alerts
|

The human β-amyloid precursor protein: biomolecular and epigenetic aspects

Abstract: Beta-amyloid precursor protein (APP) is a membrane-spanning protein with a large extracellular domain and a much smaller intracellular domain. APP plays a central role in Alzheimer's disease (AD) pathogenesis: APP processing generates β-amyloid (Aβ) peptides, which are deposited as amyloid plaques in the brains of AD individuals; point mutations and duplications of APP are causal for a subset of early-onset familial AD (FAD) (onset age < 65 years old). However, these mutations in FAD represent a very small per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 98 publications
1
30
0
Order By: Relevance
“…1b), i.e. similar to previous findings in normal skin (8). Consistent with these results, WB analysis showed that APP was highly expressed in SK tissues compared with PANST ( Fig.…”
Section: Amyloid Precursor Protein Is Highly Expressed In Seborrhoeicsupporting
confidence: 91%
See 2 more Smart Citations
“…1b), i.e. similar to previous findings in normal skin (8). Consistent with these results, WB analysis showed that APP was highly expressed in SK tissues compared with PANST ( Fig.…”
Section: Amyloid Precursor Protein Is Highly Expressed In Seborrhoeicsupporting
confidence: 91%
“…APP is an integral type I transmembrane protein, which contains at least 19 exons that are located on chromosome 21 (21q21.2-3) (6, 7). The cDNA sequence of human APP was first cloned from a brain tissue library (6,8). APP is processed by at least 3 proteases, i.e.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After a long period of time, the Aβ hydrolyzate eventually degrades. Although this had no effect on the generation of Aβ , the Aβ 1-40 level was reduced [70]. In transgenic mice, heterozygous carriers with PSEN-1/R278I mutation express higher level of neurotoxic Aβ 1-43 peptide, thus inhibiting the expression level of normal Aβ 1-40 peptide.…”
Section: Mutations In Psen Psen-1 and Psen-2mentioning
confidence: 95%
“…2.4.2.8; MIM 300800 [22][23][24]) has been reported [25][26][27]. Results of quantification of various APP-mRNA isoforms indicated an epistasis (gene-gene interactions) between mutated Hypoxanthine Phosphoribosyl Transferase 1 (HPRT1) and APP genes.…”
Section: Journal Of Rare Disorders: Diagnosis and Therapy Issn 2380-7245mentioning
confidence: 99%